The role of labour law in the protection of employees during COVID-19 pandemic in Sri Lanka - Mudalige, N.K.K.; Edirisinghe, A.A. (University of Jaffna, 2020)
The COVID19 pandemic has created an unimagined crisis that caused thousands of employees worldwide to lose their jobs, have their wages deducted, and deal with and fight against the blatant violations of labor rights benefits guaranteed to them by the existing laws. The Sri Lankan labour force saw no exception to this situation. In this context, it is essential to ascertain the efficacy of the existing legal framework in Sri Lanka in protecting the interests of the employees against adverse labour practices adopted by the employers in their favour, during the COVID-19 pandemic. Therefore, this research seeks to address whether Sri Lankan labour laws were sufficient to protect the interests of the employees during the pandemic situation. The research is carried out using three methodological approaches: the black letter approach of research empirical research methodology and the international and comparative research methodology. The findings of the research reveal the inadequacy and silence of the labour laws in Sri Lanka in addressing and dealing with the labour issues that have arisen due to COVID19 pandemic. The research lays down suggestions to reform the law in Sri Lanka to ensure the maximum protection of the employee rights and benefits against the abuses stemming from the employers' unequal bargaining power during the unfavourable times of global health emergency.
Keywords: employee interests; labour rights; role of labour law